PERANAN PENDIDIKAN TINGGI HUKUM DALAM MEMENUHI TUNTUTAN DUNIA KERJA - Charda S., Ujang (Sekolah Tinggi Hukum Bandung, 2011)
The role of higher education in law there are three responsibilities, universities, namely education, research and community service. Through dharma education, higher education law is expected to forge and produce skilled human resources who have the knowledge, so that will be donated to the community, nation and state. Through dharma research, higher education law was expected to make innovations that are useful for national development. Through the third dharma is the law of higher education acts as a motivator, mediator, problem sover, and catalyst between government interests on the one hand and the needs of society on the other. Thus, the higher education law as a vehicle and simultaneously shape the scientific community participation in development, especially development in the field of labor. Through this education, it is directed to be developed and modern nation, among others, characterized by high menunjung attitude of professionalism, respect excellence, efficiency, has a work ethic, be disciplined and have a high sense of time, aware of science and technology, constantly renew themselves through studying.Keywords: Role of Education - Employment